Effects of surface texture on wetting - Kee, Yong How (2017)
Wetting is a phenomena which occurs when a droplet tends to spread out on a surface. The extreme behaviour of wetting, also known as superhydrophilicity, is found to be useful in many real life applications and has been receiving considerable attention. In general, wetting effect of a surface can be improved by treating it with special chemicals or altering its roughness; both of which aim to change the interfacial interactions among the phases of matter involved in the system.